2015
DOI: 10.1111/1755-5922.12135
|View full text |Cite
|
Sign up to set email alerts
|

Underutilization of IV Nitrates in the Treatment of Acute Heart Failure

Abstract: SUMMARYAcute heart failure (AHF) is a growing public health concern with high inhospital mortality and costs. Clinical practice guidelines, underpinned by positive randomized controlled trials, recommend the early use of intravenous (IV) nitrates in the treatment of AHF. However, the "real-world" usage of IV nitrates has not been clearly defined. The objective of this study was to examine the use of IV nitrates in the treatment of AHF as recommended by clinical practice guidelines. A case-record analysis was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…In the ESC Heart Failure Long-Term Registry [12], Maggioni et al reported that only 20% of patients received intravenous nitrates in accordance with European guidelines. Similarly, a single-centre study carried out by Mohan et al in Scotland [17] showed that among the 49% of patients with AHF and eligible for treatment with nitrates, only 12% actually received them. Finally, in a Canadian study carried out in six EDs, only 29% of AHF patients received nitrates [18].…”
Section: Discussionmentioning
confidence: 94%
“…In the ESC Heart Failure Long-Term Registry [12], Maggioni et al reported that only 20% of patients received intravenous nitrates in accordance with European guidelines. Similarly, a single-centre study carried out by Mohan et al in Scotland [17] showed that among the 49% of patients with AHF and eligible for treatment with nitrates, only 12% actually received them. Finally, in a Canadian study carried out in six EDs, only 29% of AHF patients received nitrates [18].…”
Section: Discussionmentioning
confidence: 94%
“…Organic nitrates at low doses cause venous dilatation, whereas arteries and coronary arteries dilate at higher doses. By provoking venous and arterial dilation, intravenous nitrates can reduce the increased left ventricular filling pressures and systemic vascular resistance without affecting tissue perfusion ( 23 ), and improve stroke volume and cardiac output ( 24 ). As a result, nitrates provide marked improvement in acute pulmonary edema in which there is rapid deterioration especially in patients who have an acute rise in systemic vascular resistance and left ventricular filling pressures due to decreased baseline diastolic and systolic reserve ( 23 ).…”
Section: Nitrates Therapymentioning
confidence: 99%
“…It has been reported that only 12% of patients who were suitable for intravenous nitrate therapy received it. Those patients were more likely to have hypertension or myocardial ischemia ( 24 ). Another study reported 42% of patients with acute heart failure received nitrates who often had pulmonary edema or hypertension ( 36 ).…”
Section: Challenges With Nitrate Therapymentioning
confidence: 99%
See 2 more Smart Citations